Menggali Sektor Ekonomi Unggulan dan Berdaya Saing di Kota Bogor Tahun 2014- 2022 - Panjaitan, Rido Parulian; Nopijantoro, Wurjanto; Nugroho, Adi (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2023)
This research aims to identify the leading business sectors or fields that are the main contributors to Bogor City's GRDP in the period 2014 to 2014. currently and its development strategy. The method used uses location quotient (LQ) analysis, dynamic location quotient (LQ) analysis, and shift-share analysis. The results of the research show that the leading sectors of Bogor City that have potential for development are (1) transportation and warehousing, (2) educational services, (3) health services and social activities, and (4) other services. It is hoped that the Bogor City Government can develop development policy strategies to continue to encourage the growth of leading sectors. It is hoped that these four leading sectors can create a multiplier effect on other sectors to continue to grow and their contribution to GRDP will increase.